Ethnic Diversity and the Control of Natural Resources in Southeast Asia - Terry Rambo, A.; Gillogly, Kathleen; Hutterrer, Karl L. (Michigan Papers On South And Southeast Asia, 2020)
The authors consider the ways in which the high degree of ethnic diversity within the region is related to the nature of tropical Asian environments, on the one hand, and the nature of Southeast Asian political systems and the ways in which they manipulate natural resources, on the other. Rather than focus on defining the phenomenon of ethnicity, this book examines the different social evolutionary contexts in which the phenomenon is manifested. Companion volume to Cultural Values and Human Ecology in Southeast Asia (Michigan Papers no. 27).